Genetic Polymorphism of beta1-adrenergic Receptors and the Effect on the Clinical Efficacy of beta-adrenoblockers - V. N. Larina; M. V. Leonova (Столичная издательская компания, 2021)
Beta-adrenergic blockers are a valuable class of cardiovascular drugs and are widely used in the treatment of arterial hypertension (AH), coronary heart disease, chronic heart failure (CHF), cardiac arrhythmias, significantly improving the prognosis of patients. However, the clinical efficacy of betablockers is largely dependent on the genetic polymorphism of beta1-adrenergic receptors (ADRB1). The aim of the review was a systematic analysis of scientific data from pharmacogenetic studies on the role of beta1-adrenergic receptor polymorphism in the clinical efficacy of beta-blockers in the treatment of hypertension, chronic heart failure, and atrial fibrillation. The results of clinical trials and meta-analyzes were used. Of greatest importance is the genetic polymorphism of beta1-adrenergic receptors of two loci - Arg389Gly and Ser49Gly; the frequency of occurrence of variant and less functionally active alleles Gly389 and Gly49 in Europeans reaches 27% and 15%. The variant Gly389 allele has reduced functional activity and carriers have a weak response to the use of beta-blockers. In carriers of variant alleles Gly389 and Gly49 a reduced hypotensive effect on the use of beta-blockers was observed, and in studies of long-term efficacy, carriage of variant alleles was accompanied by an increase in the frequency and risk of unfavorable outcomes of hypertension. In pharmacogenetic studies, a reduced effect of the effect on myocardial remodeling in patients with CHF for beta-blockers in carriers of the variant Gly389 allele were confirmed. According to two meta-analyzes of trials on use of beta-blockers in patients with CHF, the frequency of increased left ventricle ejection fraction was significantly higher in carriers of the wild Arg389Arg gene type (risk ratio=1.83, p=0,001). In contrast, in atrial fibrillation, the frequency of rhythm control with beta-blockers was achieved better in the presence of the variant allele Gly389 with "loss of function". Another polymorphic Gly49 allele plays a role in desensitization and down-regulation of beta1-receptor activity, although clinically this effect has been less obvious and contradictory. However, in studies, a more pronounced clinical effect of beta-blockers was observed in carriers of the wild genotype Ser49Ser, as well as in carriers of the haplotype Ser49Ser/Arg389Arg. Thus, genetic polymorphism ADRB1 may be another important predictor of the effectiveness of beta-blockers in clinical practice, which must be taken into account in the treatment of cardiovascular diseases.